Security Economics in the European Context: Implications of the EUSECON Project - Michael Brzoska; Raphael Bossong; Eric van Um (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper presents key aspects and policy implications of a multi-annual research project on economic analyses of European security issues (EUSECON), with an emphasis on intentional threats of organised crime, piracy and terrorism. The first part argues that rational models can provide significant insights on the emergence and current patterns of terrorism and piracy. These findings could lead to new priorities or to more nuanced interventions in response to these threats. The second part focuses on the direct and indirect costs of both terrorism and organised crime. EUSECON provided new data about the scope of related illegal economic activities and explored the sensitivity of markets, societies and polities in the aftermath of terrorist attacks. It emerges that political actors are at greatest risk of over-responding, whereas mature economies display a high degree of resilience. Finally, the third part discusses economic approaches to policy evaluation. EUSECON clarified the benefits of transnational security cooperation, but also highlights the difficulties of rigorous costeffectiveness and cost-benefit calculations. Therefore, a more evidence-based approach to security policymaking, which is increasingly touted by EU decision-makers, remains elusive. In conclusion, European security policy needs further scrutiny from an economic perspective, in order to answer the increasing complexity of security challenges under the increasing financial or political constraints.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330